The role of space assets in providing for public security - (:unkn) unknown (My University, 2008)
The new security understanding in the World has come to address a wide range of threats which can be of both man-made and natural origin. Among the threats, terrorism certainly takes center stage, in terms of short term or sudden danger. But numerous other concerns for security exist, such as overt or covert development of weapons of mass destruction, organized crime, smuggling of humans and weapons, large-scale cyber attacks, and nuclear chemical or biological accidents, which may be due to a human error or outright intentional. Then there are the natural disasters, earthquakes, hurricanes, floods, droughts, and pandemics which may be of known or as yet unknown nature. © 2008 Springer Science+Business Media B.V.
Keywords: Natural disasters; Public security; Space technologies; Terrorism